Implementasi Manajemen Kepala Sekolah Terhadap Prestasi Olahraga di SD Islam Terpadu Mutiara Cendikia Kota Lubuklinggau - Heru Dirjo Joko Susanto; Satinem; Episiasi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the implementation of principal management regarding sports achievement at SD Islam Terpadu Mutiara Cendikia, Lubuklinggau. This research employs a qualitative approach. The study was conducted at SD Islam Terpadu Mutiara Cendikia in Lubuklinggau, South Sumatra Province. The informants involved all students, which is referred to as a saturated sample. Saturated sampling is a sample determination technique used when all members of the population are used as the sample. This technique is part of non-probability sampling. Data collection techniques included observation, interviews, questionnaires, and documentation. Data analysis was conducted qualitatively using the Miles and Huberman model, consisting of Data Reduction, Data Display, and Conclusion Drawing. The results of the study conclude that: Principal Management at SD Islam Terpadu Mutiara Cendikia has been implemented effectively through meticulous planning, professional coach organization, disciplined training execution, and result-based evaluation. Student Sports Achievement has shown consistent improvement, evidenced by winning medals in various local competitions. This progress is driven by an appreciation (reward) system provided by the school to high-achieving students. Key Success Factors lie in the principal's commitment to resource allocation and the ability to build a